The human cytomegalovirus 86K immediate early (IE) 2 protein requires the basic region of the TATA-box binding protein (TBP) for binding, and interacts with TBP and transcription factor TFIIB via regions of IE2 required for transcriptional regulation - Caswell, Richard; Hagemeier, Christian; Chiou, Chuang-Jiun; Hayward, Gary; Kouzarides, Tony; Sinclair, John (Journal of General Virology, 1993)
The 86K immediate early (IE) 2 protein of human cytomegalovirus trans-activates a number of homologous and heterologous promoters, including the cellular promoter for the 70K heat-shock protein (hsp 70), and the human immunodeficiency virus long terminal repeat. We have previously shown that IE2 trans-activates these two promoters in a TATA-dependent manner, and that IE2 is able to form a direct contact with TATA-box binding protein (TBP) in vitro. We now show that IE2 binds to the basic repeat region of TBP. In addition IE2 can contact a second general transcription factor, TFIIB. We have mapped the TBP- and TFIIB-binding regions within IE2 and show that these regions overlap, and also lie within parts of the protein previously identified as being required for the trans-activation and autoregulation functions of IE2.